Digital Security and Data Privacy Education for the Community of Tunggilis Village, Kalipucang, Pangandaran - Akbar, Imannudin; Titan Parama Yoga; Niswah Kaifa Nazahah (Pusat Studi Teknologi Informasi Fakultas Ilmu Komputer Universitas Bandar Lampung, 2025)
A significant gap exists in Tunggilis Village, Pangandaran between high internet adoption and low digital literacy, leaving 85% of residents vulnerable to cyber threats due to a poor understanding of privacy. In response, this Community Service Program (PKM) was designed to build awareness of cyber risks, train practical digital security skills, and initiate the formation of local literacy cadres. The program was implemented from July 21-23, 2025, utilizing a three-stage participatory approach: material presentation (Day 1), hands-on workshops (Day 2), and simulation (Day 3). An evaluation using pre- and post-tests for 42 participants showed a dramatic leap in the average comprehension score, rising from 37.1% to 94.3%. The most substantial knowledge gains were seen in topics like 2FA (+280.0%) and Digital Footprints (+362.5%), alongside achieving 100% participant understanding of OTP confidentiality. This study confirms that the hands-on workshop methodology effectively and comprehensively improved the digital literacy of the partners.